HUBUNGAN STATUS GIZI BALITA DENGAN TES MANTOUX DI POSYANDU ASTER 127 KELURAHAN KEPATIHAN KECAMATAN KALIWATES TAHUN 2024 - Wulandari, Merissa Ayu; R, Dian Aby; Kiswati, Kiswati (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Children with severely undernourished status have weak immune systems, making them more susceptible to diseases. Conversely, children suffering from tuberculosis (TB) can experience chronic nutritional issues that lead to malnutrition. Data from the Jember Kidul Community Health Center (Puskesmas) in 2023 showed that the nutritional status of toddlers based on weight-for-age (WFA) was as follows: 4.3% at risk of being overweight, 75.7% with normal nutritional status, 17.1% undernourished, and 2.8% severely undernourished. Mantoux test data from May to December 2023 at Jember Kidul Puskesmas showed that 13.8% of children tested positive. To address this issue, the government implemented mass screening through the TOSS program. The purpose of this study was to determine the relationship between the nutritional status of toddlers and the Mantoux test results at Posyandu Aster 127, Kepatihan Village, Kaliwates District, in 2024. This study used an analytical observational method with a cross-sectional design. The population consisted of 29 toddlers, with a sample size of 26 respondents, using accidental sampling techniques. The measurement tool was an observation sheet, and data analysis was conducted using the Lambda test. The nutritional status of toddlers was as follows: 3.8% severely undernourished, 38.5% undernourished, 53.8% normal nutritional status, and 3.8% at risk of being overweight. The Mantoux test results showed 15.4% positive and 84.6% negative. Data analysis revealed a p-value of 0.308. There is no relationship between the nutritional status of toddlers and the Mantoux test results at Posyandu Aster 127, Kepatihan Village, Kaliwates District, in 2024. Parents are advised to pay attention to their children's nutritional intake by providing a balanced diet and not hesitate to seek medical treatment immediately if their child becomes ill. ABSTRAKAnak dengan status gizi sangat kurang memiliki daya tahan tubuh yang lemah sehingga mudah terserang penyakit. Begitu pula sebaliknya, anak yang mengidap TBC bisa memicu masalah gizi kronis yang berujung pada gizi buruk. Data dari Puskesmas Jember Kidul, status gizi balita menurut BB/U pada tahun 2023 adalah 4,3% gizi resiko berat badan lebih, 75,7% gizi normal, 17,1 % gizi kurang, dan 2,8 % gizi sangat kurang. Data tes mantoux bulan Mei s/d Desember 2023 di Puskesmas Jember Kidul 13,8% dengan hasil tes positif. Untuk mengatasi hal tersebut, pemerintah melakukan penapisan besar-besaran dengan program TOSS. Tujuan penelitian untuk mengetahui hubungan antara status gizi balita dengan tes mantoux di Posyandu Aster 127 Kelurahan Kepatihan Kecamatan Kaliwates Tahun 2024. Observasional analitik dengan rancangan Cross Sectional. Populasi sebanyak 29 balita, dengan sampel sebanyak 26 responden, menggunakan teknik Accidental sampling. Alat ukur lembar observasi dengan menggunakan uji Lambda. Status gizi sangat kurang (severaly underweight) 3,8%, status gizi kurang (underweight) 38,5%, status gizi normal 53,8%, dan status gizi resiko berat badan lebih 3,8%. Tes Mantoux positif 15,4%, tes Mantoux negatif 84,6%. Hasil analisis data diperoleh p value 0,308. Tidak ada hubungan antara status gizi balita dengan tes Mantoux di Posyandu Aster 127 Kelurahan Kepatihan Kecamatan Kaliwates Tahun 2024. Diharapkan orang tua untuk memperhatikan asupan gizi balitanya dengan menu gizi seimbang dan tidak takut untuk segera membawa anaknya berobat apabila sakit.